Agency in Silence: The Case of Unaccompanied Eritrean Refugee Minors in the Netherlands - Kusmallah, Nebil (2024)
Following the so‐called refugee crisis, unaccompanied refugee minors (URMs) from Eritrea were portrayed negatively in Europe. Although such portrayals are often amplified by media and policy discourses, the main reasons for this negative view were a lack of understanding of URMs’ subjectivities, the institutional silencing process they face in their everyday lives, and the ways they show agency in such precarity. This article addresses institutional silencing practices that Eritrean URMs encounter and the various ways they engage with them. Using data gathered during 2016–2018 from Eritrean URMs in the Netherlands, we explore how participants navigate the exclusionary processes they encounter in relation to institutions, such as refugee reception centres, refugee protection organizations, immigration authorities, and schools. Inspired by Sherry Ortner’s and Saba Mahmood’s work, we show the importance of less dominant forms of agency (delayed or docile forms) in how URMs engage with the power of institutional silencing practices. We then show the (often unseen) agency of these young people as the desire of the “less powerful” or “less resourceful” to “play their own serious games even as more powerful parties seek to devalue and even destroy them” (Ortner, 2006, p. 147).